Microtubule-associated protein tau genetic variations are uncommon cause of frontotemporal dementia in south India - Aswathy, P.M. (2013)
Microtubule-associated protein tau (MAPT) positive neuropathology is the characteristic feature of majority of frontotemporal dementia (FTD) cases, which is due to the mutations or haplotypic variations in the gene encoding MAPT (MAPT). The present study was aimed at determining the frequency of genetic variations in MAPT in a south Indian FTD cohort. The frequency of mutations were determined in 116 FTD, 8 progressive supranuclear palsy (PSP) and 3 corticobasal syndrome (CBS) patients and haplotype diversity were analyzed in a study cohort comprising 116 FTD, 8 PSP, 3 CBS, 194 other dementia groups, 78 mild cognitive impairment (MCI) and 130 cognitively normal individuals and report no pathogenic mutations in FTD/PSP/CBS or haplotypic association with disease risk in FTD or other dementia patients. These findings suggest that there may be other genetic or epigenetic factors contributing to the pathogenesis of FTD in the south Indian population.